Effect of Atorvastatin and Losartan on Glomerular Filtration Rate in Patients With Mild to Moderate Chronic Kidney Disease (KYAMC Journal, 2019)
Background: Atorvastatin, a member of HMG CO-A reductase inhibitors, has been shown to have renoprotective effect in patients with Chronic Kidney Disease (CKD). Statins are supposed to decrease the oxidized lipid particles, suppress the activity of inflammatory mediators and prevent vascular thrombosis and thus could minimize renal cell damage. Losartan, an antihypertensive drug also diminishes proteinuria in patients with chronic kidney diseases or diabetes mellitus. Therefore the effect of concurrent use of atorvastatin and losartan on Glomerular Filtration Rate (GFR) could be a matter of interest from both Pharmacological and Clinical perspective.Objective: To assess the renoprotective effect of atorvastatin and losartan in patients with chronic kidney disease treated at Bangabandhu Sheikh Mujib Medical University (BSMMU).Materials and Method: Total forty four (44) patients suffering from CKD (stage one to stage three) were enrolled into two groups. Patients in Group A, received atorvastatin (10 mg) and losartan (50 mg) once daily for eight weeks. Patients in Group B, received losartan but not atorvastatin for the same duration. Serum creatinine level was measured at the commencement and also after eight weeks to calculate estimated glomerular filtration rate (eGFR) in individual patients with MDRD (Modification of Diet in Renal Disease) study equation.Results: There was significant (P < 0.001) reduction of Serum Creatinine and significant (P < 0.001) increase in e GFR in the patients, treated with atorvastatin and losartan.Conclusion: Concurrent administration of atorvastatin and losartan increased glomerular filtration rate (GFR) significantly in patients with chronic kidney disease.KYAMC Journal Vol. 10, No.-1, April 2019, Page 43-47